1999
DOI: 10.1590/s0100-06831999000100008
|View full text |Cite
|
Sign up to set email alerts
|

Quantificação de micélio extrarradicular de fungos micorrízicos arbusculares em plantas cítricas: II. Comparação entre diferentes espécies cítricas e endófitos

Abstract: RESUMOVisando verificar a influência da utilização de diferentes métodos de quantificação de micélio extrarradicular ativo (MEA) e micélio extrarradicular total (MET) de fungos micorrízicos arbusculares (FMAs) e de diferentes hospedeiros nesta simbiose, foi realizado um experimento em casa de vegetação, com delineamento inteiramente casualizado e esquema fatorial: 3 espécies de FMAs (Glomus intraradices, G. etunicatum e G. clarum) e um controle sem FMA x 6 doses de P (0, 50, 100, 150, 200 e 250 mg kg -1 de sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
0
5
1
7
Order By: Relevance
“…These results conflict with previous findings in which the AEM decreased with P increase (Nogueira & Cardoso, 2000) or remained stable (Cardoso-Filho et al, 1999;Nogueira & Cardoso, 2006) but corroborate another work in which the AEM increased, depending on the host plant (Melloni & Cardoso, 1999b). The amount of AEM, less than 2.0 m g -1 , was comparable to that found in citrus experiments (Melloni & Cardoso, 1999b), but lower than in experiments with maize (Cardoso-Filho et al, 1999), who found up to 12 m g -1 , depending on the P level and plant age. Probably the host plant exerts direct effect on the AEM production.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…These results conflict with previous findings in which the AEM decreased with P increase (Nogueira & Cardoso, 2000) or remained stable (Cardoso-Filho et al, 1999;Nogueira & Cardoso, 2006) but corroborate another work in which the AEM increased, depending on the host plant (Melloni & Cardoso, 1999b). The amount of AEM, less than 2.0 m g -1 , was comparable to that found in citrus experiments (Melloni & Cardoso, 1999b), but lower than in experiments with maize (Cardoso-Filho et al, 1999), who found up to 12 m g -1 , depending on the P level and plant age. Probably the host plant exerts direct effect on the AEM production.…”
Section: Resultscontrasting
confidence: 99%
“…The amount of TEM found in this experiment was comparable to previous findings (Sylvia, 1988;Cardoso-Filho et al, 1999;Andrade et al, 2005;Nogueira & Cardoso, 2006). Other evaluations for hyphal lengths of filamentous fungi under natural conditions, however, reached even much higher values, up to more than 100 m cm -3 of soil (Miller et al, 1995). Although the differentiation of mycorrhizal hyphae from that of other filamentous fungi in the soil is quite difficult (Sylvia, 1992), at least 35 to 70% of the total is expected to be from mycorrhizal fungi (Cardoso-Filho et al, 1999).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Foram montadas cinco lâminas por repetição, com dez segmentos de raiz por lâmina. A contagem dos segmentos colonizados foi feita com auxílio de microscópio ótico (100x), conforme descrito por Melloni e Cardoso (1999). A colonização micorrízica foi estimada em valor percentual, considerando-se os segmentos colonizados em relação ao total de segmentos analisados.…”
Section: Os Fungos Micorrízicos Arbusculares (Fma)unclassified